170k views
4 votes
Solve for x in the equation
I need help ASAP​

Solve for x in the equation I need help ASAP​-example-1
User Schooner
by
4.9k points

2 Answers

2 votes

Answer:

D

Explanation:

Given

2x² + 3x - 7 = x² + 5x + 39

Subtract x² + 5x + 39 from both sides

x² - 2x - 46 = 0 ← in standard form

with a = 1, b = - 2, c = - 46

Solve for x using the quadratic formula

x = (- (- 2) ±
√((-2)^2-(4(1)(-46)) ) / 2

= ( 2 ±
√(4+184) ) / 2

= ( 2 ±
√(188) ) / 2

= ( 2 ± 2
√(47) ) / 2

= 1 ±
√(47)

User Beasone
by
5.6k points
4 votes
The answer is D

You just move all numbers to the left and set it equal to 0
And then you add all same variables together
After that you use the quadratic formula
User Erga Kandly
by
5.4k points